Implementation of Training Management for Leadership Development - Nindya Azzahrah; Syafri Fadillah Marpaung (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to analyze the implementation of training management in supporting leadership development, identify obstacles encountered, and formulate effective strategies. The research method used is a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies. The results of the study indicate that: the implementation of training management has been carried out systematically through the stages of planning, implementation, and evaluation. Training planning is based on competency needs, HR nomination results, and the results of coordination with educational and industrial stakeholders. The training implementation uses a blended learning approach and involves professional instructors from both internal and external sources. Training evaluation is conducted using an outcomes-based model to ensure participants can apply leadership skills in the workplace. The main obstacles faced include the high turnover of school principals that hinders program sustainability, limited teacher participation due to geographical and information constraints, and the limited number of experienced instructors. However, BBPPMPV BBL has responded to these challenges by developing an online monitoring system, expanding partnerships, and refining the mapping of training needs periodically. Strategies to improve the effectiveness of training management are carried out through a cross-sectoral collaborative approach, the integration of a merit system in participant selection, and an emphasis on strengthening leadership character based on the values of integrity, adaptability, and innovation. The Teaching Factory approach is an important part of forming leaders who are resilient, solution-oriented, and responsive to change.